Explore the properties of $$Λ (1670)$$ Λ ( 1670 ) in the Cabibbo-favored process $$Λ ^+_c → p K^- π ^+$$ Λ c + → p K - π + - Sheng-Chao Zhang; Man-Yu Duan; Wen-Tao Lyu; Guan-Ying Wang; Jing-Yu Zhu; En Wang (European Physical Journal C: Particles and Fields)
Abstract Recently, the Belle and LHCb Collaborations have measured the $$Λ ^+_c → p K^- π ^+$$ Λ c + → p K - π + decay and reported the $$K^- p$$ K - p invariant mass distribution, which shows a clear cusp structure around the $$η Λ $$ η Λ threshold. In this work, we have analyzed this process by considering the triangle mechanism and the S-wave pseudoscalar meson-octet baryon interactions within the chiral unitary approach, which dynamically generates the $$Λ (1670)$$ Λ ( 1670 ) . Our results are in good agreement with the Belle measurements, which implies that the cusp structure around $$η Λ $$ η Λ threshold could be associated with the $$Λ (1670)$$ Λ ( 1670 ) with the molecular nature.